Diversity and Composition of Aquatic and Riparian Plants in Lake Tondano, North Sulawesi - Norma Josefin Dapas, Farha; Lengkong, Johny; Dapas, Servie; Lombogia, Stanly; Ladisa, Stevia (Biosfer: Jurnal Tadris Biologi, 2026)
Aquatic and riparian vegetation plays a fundamental role in maintaining freshwater ecosystem structure, biodiversity, and ecological processes. However, increasing environmental pressures have altered vegetation communities in many tropical lakes, including Lake Tondano, Indonesia. This study aimed to analyze the diversity and composition of aquatic and riparian plants in Lake Tondano as baseline information for evaluating ecosystem condition. A quantitative ecological survey was conducted at three sampling stations, namely Tounelet, Eris, and Taler villages, using purposively selected stations and randomly established plots. Aquatic plants were sampled using 1 × 1 m² quadrats at a maximum water depth of 2 m, whereas riparian vegetation was surveyed using 10-m transects established perpendicular to the shoreline. Plant species were identified through field observations and laboratory verification, and vegetation data were analyzed using the Shannon–Wiener Diversity Index and the Importance Value Index. A total of 21 plant species were recorded, consisting of three aquatic species and eighteen riparian species belonging to eleven plant families. Aquatic vegetation exhibited low species diversity, whereas riparian vegetation showed moderate diversity and greater taxonomic richness. The vegetation community was dominated by several invasive and disturbance-tolerant species, particularly Eichhornia crassipes in aquatic habitats and herbaceous species in the riparian zone. These findings indicate that vegetation composition in Lake Tondano reflects ecological pressures affecting freshwater habitats. This study provides baseline ecological information that may support future biodiversity monitoring, conservation planning, and sustainable management of aquatic and riparian ecosystems in Lake Tondano. Keanekaragaman dan Komposisi Vegetasi Air serta Vegetasi Riparian di Danau Tondano, Sulawesi Utara ABSTRAK: Tumbuhan air dan tumbuhan riparian memiliki peran penting dalam menjaga struktur, fungsi, dan keberlanjutan ekosistem perairan tawar. Namun, tekanan lingkungan yang semakin meningkat telah memengaruhi komposisi vegetasi di berbagai danau tropis, termasuk Danau Tondano, Sulawesi Utara. Penelitian ini bertujuan untuk menganalisis keanekaragaman dan komposisi tumbuhan air serta tumbuhan riparian di Danau Tondano sebagai informasi dasar dalam mengevaluasi kondisi ekosistem danau. Penelitian menggunakan pendekatan survei ekologi kuantitatif pada tiga stasiun pengamatan, yaitu Desa Tounelet, Desa Eris, dan Desa Taler, yang dipilih menggunakan teknik purposively selected stations and randomly established plots. Tumbuhan air disampling menggunakan kuadrat berukuran 1 × 1 m² pada kedalaman maksimum 2 m, sedangkan tumbuhan riparian diamati menggunakan transek sepanjang 10 m yang ditarik tegak lurus dari tepian danau ke arah daratan. Identifikasi spesies dilakukan melalui observasi lapangan dan verifikasi laboratorium, sedangkan analisis data menggunakan Indeks Keanekaragaman Shannon–Wiener dan Indeks Nilai Penting. Hasil penelitian menunjukkan bahwa terdapat 21 spesies tumbuhan yang terdiri atas 3 spesies tumbuhan air dan 18 spesies tumbuhan riparian yang termasuk dalam 11 famili. Keanekaragaman tumbuhan air tergolong rendah, sedangkan tumbuhan riparian menunjukkan keanekaragaman sedang dengan kekayaan taksonomi yang lebih tinggi. Komunitas vegetasi didominasi oleh beberapa spesies invasif dan toleran terhadap gangguan, terutama Eichhornia crassipes pada habitat perairan. Temuan ini memberikan informasi dasar yang penting untuk mendukung pemantauan keanekaragaman hayati, konservasi, dan pengelolaan berkelanjutan ekosistem Danau Tondano.